Type a botulinum toxin in the management of spontaneous salivary otorrhea: a case report - Teffran J. Chan; Trevor A. Lewis; Doron D. Sommer (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Spontaneous salivary otorrhea is a rare presentation only previously documented twice in literature where parotid salivary secretions are found in the external auditory canal. Conventional treatment of spontaneous parotid salivary fistulas includes surgical management with interposed grafts, fistula tract ablation, and possible superficial parotidectomy. Associated risks include facial nerve injury, Frey syndrome and facial scarring. Here we report the first case of spontaneous salivary otorrhea conservatively managed with a type A botulinum toxin (BTA) injection. Case presentation A 17-year-old female presented with a 5-month history of left sided otorrhea and transient left facial swelling associated with gustatory stimulation. The otorrhea fluid tested positive for salivary amylase and negative for beta 2 transferrin. Fifty units of BTA were injected into the left parotid gland under ultrasound guidance. Cessation of symptoms was achieved 3 weeks after intervention. The patient remains symptom-free at the 2 year follow up. Conclusion BTA injection was well tolerated under ultrasound guidance and has led to long-term resolution of the patient’s symptoms. BTA injection appears to be a safe and effective way to conservatively manage this rare presentation of spontaneous salivary otorrhea.